Fundamental principles of positron emission tomography (PET) 2 - Mawlawi, Osama (Henry Stewart Talks, 2010)
Aspects of PET imaging, Image reconstruction, Filtered Back Projection, Iterative reconstruction, Reconstruction comparison, Factors affecting scanner sensitivity, 2D and 3D, Increase in sensitivity in 3D over 2D, Disadvantages of 3D imaging: loss of contrast & image quality, Improved sensitivity, Quantitative PET performance, Phantom study, Motion effects, Partial volume effect, PET data acquisition schemes, Static & dynamic modes, Gated PET, Time of flight (TOF) acquisition, Hybrid scanner: PET/CT imaging, Rationale of PET/CT, Types of artifacts, Current PET/CT scanner status, Different types of PET/CT scanners, Radiation exposure, Available dosimetry tools, PET applications, Scanning Melanoma, Lymphoma and Brain Astrocytoma, Imaging in Neurology: Parkinson's disease, Receptor binding, Imaging in Cardiology
Reviewed at 2020/09/11, Updated at 2022/07/14